Medical Microbiology & Immunology : Examination & Board Review - Levinson, Warren E.; Jawetz, Ernest (Connecticut : Appleton & Lange, 1994)
McGraw-Hill Professional Publishing, 2002. Paperback. Good. Pages can have notes/highlighting. Spine may show signs of wear. ~ ThriftBooks: Read More, Spend Less.Dust jacket quality is not guaranteed. What students are saying about previous editions of Levinson & Jawetz's Medical Microbiology and Immunology "I'm a second-year medical student... I just had to take a minute and let you know how helpful this book has been in preparing for our infectious disease course and upcoming board exam. The book (is) well written and clear in stressing the important material. Thank you." "...the best read I've had in medical school! "Clear, concise text together with well organized summary tables and carefully designed study questions make this book extremely useful for time-efficient study and review of immunology, microbiology and parasi tology." Basic and clinical aspects of immunology, bacteriology, virology, mycology, and parasitology are comprehensively covered in this edition. Relevant information is presented in a concise and interesting manner and combines text, summaries, case studies, and USMLE practice questions in both microbiology and immunology.
Table of Contens -- Preface -- Acknowledgments -- Part. 1. Basic Bacteriology. -- Part. 2. Clinical Bacteriology. -- Part. 3. Basic Virology. -- Part. 4. Clinical Virology. -- Part. 5. Mycology. -- Part. 6. Parasitology. -- Part. 7. Inmunolgy. -- Part. 8. Brief Summaries of Medically Important Organisms -- Part, 9. Clinical Cases. -- Part. 10. USMLE. Practice Questions. -- Part. 11: USMLE. Practice Examination.
Keywords: MICROBIOLOGÍA; INMUNOLOGÍA